A Central Limit Theorem for Random Walks on the Dual of a Compact Grassmannian - Rösler, Margit; Voit, Michael (Symmetry, Integrability and Geometry: Methods and Applications)
Keywords: Geometry and Topology; Mathematical Physics; Analysis

Equivariant spectral asymptotics forh-pseudodifferential operators - Weich, Tobias (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Manifestation of Berry’s Phase in Nuclear Quadrupole Resonance Spectra of Rotating Powder Samples - Sinyavsky, Nikolay; Maćkowiak, Mariusz; Schmidt, Claudia (Zeitschrift für Naturforschung A)
The effect of Berry’s phase on the nuclear quadrupole resonance (NQR) spectra of rotating powder samples is studied experimentally, and its application for the determination of the electric field gradient asymmetry η is demonstrated. The NQR frequency splittings, which are observed for the spin 3/2 nucleus of 35 Cl in powder samples of p-dichlorobenzene (C 6 H 4 Cl 2 ) and cyanuric chloride (C 3 N 3 Cl 3 ), are interpreted as a manifestation of Berry’s phase, associated with the adiabatically changing Hamiltonian due to sample rotation. The accumulation of Berry’s phase during the rotation process is responsible for the observed dependence of the NQR line shape on the rotation frequency and the asymmetry parameter. The proposed method for the determination of η involves the analysis of the NQR powder patterns of the rotating samples.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy; Mathematical Physics

A Limit Relation for Dunkl-Bessel Functions of Type A and B - Rösler, Margit; Voit, Michael (Symmetry, Integrability and Geometry: Methods and Applications)
Keywords: Geometry and Topology; Mathematical Physics; Analysis